A comparative study on microwave assisted dyeing properties of conventional and recycled polyester fabrics - YILMAZ, BURCU (My University, 2023)
In the literature, microwave studies are predominantly on cellulosic based fabrics and there are limited studies in microwave assisted polyester dyeing. Today, due to the interest in recycled polyester, it was decided to study conventional and microwave heating in the exhaust dyeing methods of recycled polyester and conventional polyester fabrics. The aim of the study was to determine whether microwave heating could be used to shorten dyeing process times and to obtain dyeing with sufficient colour fastness. Accordingly, two samples, 100% polyester and 62% recycled polyester 38% polyester woven fabrics, are used. The samples were dyed with 1.5% Bemacron Smart Red EE disperse dye. The colorimetric properties, colour fastnesses and tear strength of the dyed fabrics were investigated and compared with each other. Spectrophotometer measurements were evaluated that 100% polyester fabric dyed with the microwave method had a darker colour compared to the conventional method, on the other hand, there was no significant colour difference between the conventional and microwave dyeing method of the 62% recycled polyester 38% polyester woven fabric. Colour fastness test results were evaluated that all the fastness results of the recycled and conventional polyester fabrics in the microwave tests were obtained 4 and 4-5. The advantages of microwave heating over the conventional method are that the dyebath heats up in a short time and gives good colour fastnesses without any deterioration in the properties of dyed materials.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Engineering, Computing & Technology (ENG); ENGINEERING; Genel Mühendislik; Fizik Bilimleri; General Engineering; Physical Sciences; Dyeing; Microwave; Polyester fabric; Recycle